Ionic shape memory polymer gels as multifunctional sensors. Issue 36 (30th August 2022) - An, YingJun; Yoshida, Haruki; Jing, Yuxin; Liang, Tian; Okuzaki, Hidenori
Abstract : The wearable shape memory multifunctional sensor array is capable of sensing both direction and quantity of bending displacement and velocity. Abstract : Novel ionic shape memory polymer (SMP) gels were fabricated using SMPs and ionic liquids (ILs) of 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMI-TFSI) at different weight ratios ( W IL ). The shape memory effect and sensor performance of the ionic SMP gels were investigated by means of thermomechanical and mechanoelectrical analyses. It was found that the ionic SMP gel at W IL = 25 wt% showed a shape memory effect with the shape fixing ratio ( R f ) and shape recovery ratio ( R r ) of 72.7% and 72.9%, respectively. Upon bending, the ionic SMP gel sensors with PEDOT:PSS electrodes generated an open circuit voltage of 3.3 mV and a charge of 1.6 nC which linearly increased with increasing bending displacement and velocity, respectively. Furthermore, the wearable shape memory multifunctional sensor array was demonstrated as a self-powered motion sensor for IoT applications.